CALF CIRCUMFERENCE AT BIRTH: A SCREENING METHOD FOR DETECTION OF LOW BIRTH WEIGHT - Kumar, Sandip; Jaiswal, K; Dabral, M; Dabral, M; Malhotra, A K; Malhotra, A K; Verma, B L (Indian Journal of Community Health, 2012)
Background: Low Birth Weight (LBW) babies run a higher risk of morbidity and mortality in the perinatal period. However, in our country where almost 70-80% births take place at home and peripheral hospitals, taking accurate weight is a problem due to unavailability of weighing scale and trained personnel. Hence there is a constant search for newer methods to detect LBW babies so that early interventions can be instituted. Various authors have used different surrogate anthropometric measurements from different parts of our country. In the present study, an attempt was made to validate the feasibility of using calf circumference as a predictor of LBW babies that can be used by a trained or untrained person. Objectives: To study various anthropometric measurements including calf circumference in newborns and to correlate various measurements with birth weight. Methods: The present study was conducted in the department of Social & Preventive Medicine, MLB Medical College, Jhansi (UP) for a period of one year. The study included 1100 consecutively delivered neonates in the maternity ward of MLB Medical College Hospital, Jhansi (UP). The birth weight (Wt), crown heel length (CHL), crown rump length (CRL), head circumference (HC), chest circumference (CC), mid arm circumference (MAC), thigh circumference (TC) and calf circumference (CC) by standard techniques. All the measurements were taken by a single person throughout the study period with in 24 hours of delivery. Standard statistical methods were adopted for determination of critical limit, sensitivity, specificity and correlation coefficient of different anthropometric measurements in relation to birth weight. Results: Analysis of data indicates that out of 1100 newborns, 55.64% were low birth weight. The percentage of newborns > 2500gm was 44.36. Overall average birth weight was 2348 ± 505gm. Out of 1100 newborns, 608 (55.27%) were males and 492 (44.73%) were females. Average birth weight for males was 2412 ± 482gm and for females it was 2272 ± 502gm out of 1100 newborns, 608 (55.27%) were males and 492 (44.73%) were females. Average birth weight for males was 2412 ± 482gm and for females it was 2272 ± 502gm. The highest sensitivity for detecting LBW babies was seen with calf circumference (98.4%) followed by thigh circumference (91.6%). The specificity of calf circumference was less than that of thigh circumference; it was 92.0% and 96.2% respectively. Conclusion: Calf circumference is a simple, cheap, reliable and quick indicator for predicting LBW babies in the community. Furthermore, it is easy to train traditional birth attendants to screen out high risk group new bourns by simply measuring the calf circumference.